Exit Behaviors Of Credit Cardholders In Selected Local Banks In Malaysia - Abdul Halim, Ahmad Subky (2005)
This research based study focuses on credit cardholder's exit behavior of selected banks in general and in particular their resolution efforts with credit card problems and the likelihood of exiting , that is, discontinuing the use of a given credit card or of the financial institution associated with the card. The study of Consumer Behavior was of the prime interest, as failure to adhere to the principle shall prove futile and lead to exit behaviors.